Pengaruh Disiplin Kerja Dan Tanggung Jawab Kerja terhadap Komitmen Organisasi Pegawai Pada Badan Perencanaan Pembangunan Daerah Kota Padang - Sanenek, Monalisa; Delvianti, Delvianti; Agussalim, Agussalim (Jurnal Riset dan Sains Ekonomi, 2025)
This research aims to determine which indicators are dominant in work discipline, work responsibility and organizational commitment of employees at the Padang City Regional Development Planning Agency and work discipline and work responsibility for employee organizational commitment at the Padang City Regional Development Planning Agency partially and simultaneously. Research This uses a quantitative approach. The research sample was 52 respondents. Data collection uses a valid and reliable questionnaire. Data analysis was carried out using multiple linear regression analysis, testing determinant coefficients of t and F hypotheses. Research results. The dominant indicator of the organizational commitment variable is the affective commitment indicator with a TCR value of 87.20%, the work discipline variable has a monitoring indicator. inherent with a TCR value of 81.20% and the work responsibility variable has a dominant indicator of capability with a TCR value of 80.80% and work discipline and work responsibility have a positif and significant effect on the organizational commitment of employees at the Padang City Regional Development Planning Agency partially and simultaneously.